A 7th-Century Necklace from Hardingstone, Northamptonshire, England. Issue 2 (3rd July 2018) - HAWORTH, KATIE
Abstract : A NECKLACE ASSEMBLAGE from a small Anglo–Saxon cemetery in Hardingstone (Northamptonshire), was discovered during excavations in the 1960s, but until now has remained unpublished. It is an example of a type commonly found in the distinctive well-furnished female graves of the later 7th century in England and is constituted from beads and pendants, some of unusual type. This paper investigates this discovery, individually assessing the component parts of the necklace and presenting qualitative compositional analysis of the silver and glass used in their manufacture. As a case study, the Hardingstone necklace provides an opportunity to explore the meaning of these kinds of jewellery item and to better understand the prominent role of the women who wore them in 7th-century Anglo-Saxon society.